Evidence on Policies to Increase the Development Impacts of International Migration - McKenzie, David; Yang, Dean (Oxford University Press on behalf of the World Bank, 2017)
International migration offers individuals and their families the potential to experience immediate and large gains in their incomes and offers a number of other positive benefits to the sending communities and countries. However, there are also concerns about the potential costs of migration, including concerns about trafficking and human rights, a desire for remittances to be used more effectively, and concerns about a loss of externalities from skilled workers. As a result, there is increasing interest in policies that can enhance the development benefits of international migration and mitigate these potential costs. We provide a critical review of recent research on the effectiveness of these policies at three stages of the migration process: pre-departure, during migration, and directed towards possible return. The existing evidence base suggests some areas of policy success: bilateral migration agreements for countries whose workers have few other migration options, developing new savings and remittance products that allow migrants more control over how their money is used, and efforts to provide financial education to migrants and their families. Suggestive evidence, together with theory, offers support for a number of other policies, such as lowering the cost of remittances, reducing passport costs, offering dual citizenship, and removing exit barriers to migration. Research offers reasons to be cautious about some policies, including policies enforcing strong rights for migrants, such as high minimum wages. Nevertheless, we find the evidence base to be weak for many policies, with no reliable research on the impact of most return migration programs or whether countries should attempt to induce communal remitting through matching funds.